Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

Technology and Teacher Professional Development in Tanzania: Research instruments pack - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chachage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
This pack contains links to research instruments developed by EdTech Hub, Aga Khan University, and Tanzania Institute of Education for a study investigating the impact of a national teacher professional development programme on primary-level learning outcomes. The tools have been developed iteratively, with substantive piloting having taken place, both in workshop settings and in schools. They draw on good practice examples, such as the World Bank’s TEACH tool for classroom observation and other research projects the team have worked on. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit.
ZenodoArchiveID: 7691834 ZenodoArchiveConcept: 7691833 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7434218 10.5281/zenodo.7691834 10.53832/edtechhub.0148 2405685:GXM765F3
Keywords: _r:AddedByZotZen

Developing dialogic classroom practices through supporting professional agency: Teachers’ experiences of using the T-SEDA practitioner-led inquiry approach - Calcagni, Elisa; Ahmed, Farah; Trigo-Clapés, Ana Laura; Kershner, Ruth; Hennessy, Sara (Teaching and Teacher Education, 2023)
Classroom dialogue is considered productive for learning but rarely observed, and practitioner professional development is needed. This study investigated how 67 teachers across educational phases in six countries contextualised the T-SEDA inquiry toolkit to conduct classroom inquiries and develop new practices. Surveys and inquiry reports yielded insights into how practitioner agency was further developed, with implications for sustainability. Change was evident in self-reported enhanced awareness and understanding of dialogue and use of dialogic strategies. Increases in students’ dialogic participation and plans for dissemination to colleagues were reported.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2023.104067 2405685:ZQQP3GIM
Keywords: Classroom dialogue; Dialogic teaching; Professional development; Professional learning; Reflective inquiry; Teacher agency

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7948836 ZenodoArchiveConcept: 7948835 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7948836 10.53832/edtechhub.0166 2339240:N4CC2DD8 2405685:FICAJDR3 2405685:HUR5C9QN 2405685:XVCIV366
Keywords: _r:AddedByZotZen

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6817992 10.53832/edtechhub.0171 2405685:KAAC2B78
Keywords: _r:AddedByZotZen

Uzoefu wa Walimu katika kufundisha kwa kutumia teknolojia nchini Tanzania Mapendekezo Juu ya Sera na Utekelezaji - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2023)
This is a Swahili version of the policy brief Teachers’ Experiences of Teaching With Technology in Tanzania: Recommendations for policy and practice published in October 2022. Muhtasari huu wa masuala ya kisera unatoa ripoti ya utafiti wa walimu nchini Tanzania (Julai-Novemba 2021) ambao EdTech Hub iliagiza HakiElimu kuufanya ili kuchangia taarifa itakayosaidia mchakato endelevu wa serikali kuleta mageuzi ya MEWAKA katika ngazi za shule na vituo vya walimu. Dodoso zilichukuliwa kutoka katika uchunguzi wa kihistoria wa kimataifa uliohusisha takriban walimu 20,000+ , kuhusu uzoefu na changamoto zao katika ufikiaji na matumizi ya EdTech, ufundishaji na ujifunzaji, na maendeleo ya kitaaluma katika mwaka 2021, iliyoripotiwa na timu kutoka T4 Education na EdTech Hub. Maneno muhimu: teknolojia ya elimu; matokeo ya kujifunza; mahitaji ya mwalimu; mafunzo endelevu ya taaluma ya ualimu; sauti ya mwalimu / Kauli ya mwalimu; ufikiaji wa teknolojia An output of the EdTech Hub, https://edtechhub.org
DOI 10.53832/edtechhub.0147 ZenodoArchiveID: 7652491 ZenodoArchiveConcept: 7652490 2405685:ECXPS38I KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8363989 10.53832/edtechhub.0174 2405685:ECXPS38I 2405685:MDC3E34G
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7966434 ZenodoArchiveConcept: 7966433 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7966434 10.53832/edtechhub.0168 2405685:CQ8JNCH8
Keywords: _r:AddedByZotZen

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

Usability Testing of a Mobile-based Learning Management System for Teacher Continuous Professional Development in Tanzania - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Haßler, Björn; Proctor, Jamie; EdTech Hub (The International Journal of Education and Development using Information and Communication Technology, 2023)
The last two decades have seen the growing adoption of mobile devices to enhance the quality of teachers' continuous professional development (TCPD) in low-income countries. Using mobile devices, typically not designed for educational use, presents new usability challenges, preventing teachers from effectively accessing learning materials in learning management systems (LMS). Therefore, it is important to test usability to improve the delivery of TCPD via mobile devices. This study evaluated the usability of TCPD-focused mobile-based LMS accessed via a mobile web browser and mobile app. The evaluation used a hybrid think-aloud method involving 63 teachers from 12 schools in Tanzania. Half of the schools were evaluated using a concurrent think-aloud method, and the other half using a retrospective think-aloud method. The study found that teachers encountered many usability problems in using the mobile app compared to those who accessed the LMS via mobile web browsers. The study also found usability flaws in the registration and login process, poor language translation, technical errors, and issues with quiz questions. These findings show the importance of user testing, even for well-developed LMS, such as Moodle. Additionally, this work provides useful guidance for those who want to implement mobile learning via an LMS in low-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:ZTWSB6CB 2405685:L5AY2YZI
Keywords: ⛔ No DOI found

MEWAKA in Tanzania: Emerging findings on tech-supported teacher professional development - Koomar, Saalim; Massam, Winston; Anthony, Gervace; Mrope, Winifrida; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fredrick; Proctor, Jamie; Komba, Aneth; Mwakabungu, Fika; Barretto, Johnpaul; Barretto, Winston Massam, Gervace Anthony, Winifrida Mrope, Taskeen Adam, Sara Hennessy, Fredrick Mtenzi, Jamie Proctor, Aneth Komba, Fika Mwakabungu and Johnpaul, Saalim Koomar (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teachers’ Continuous Professional Development (TCPD)) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The programme is decentralised, with teacher learning based in schools and focused on semi-structured Communities of Learning (CoLs). CoLs are spaces where teachers can gather weekly to discuss and reflect on issues most relevant to their schools as well as learn and improve their pedagogical skills. Peer facilitators help teachers to collaboratively solve problems, learn new approaches to improve their practice, and generally create a culture of reflection and school improvement.
KerkoCite.ItemAlsoKnownAs: 2339240:AQZAQSU7 2405685:KMN7H8UA

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521062 ZenodoArchiveConcept: 7521061 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521062 10.53832/edtechhub.0145 2405685:M3D6NGR4 2405685:WVRHTVIZ 2486141:V94NMZIU
Keywords: _r:AddedByZotZen

Lessons on technology-enabled teacher professional development from Bangladesh’s national curriculum reform - Ahmed, Shakil; Mazari, Haani; Hassan, Mehdi; Azam, Shafiul; Sidotam, Annie; Clarke-Wilson, Alison; Sarwar, Md Afzal Hossain (EdTech Hub, 2023)
This blog presents Part 1 of our lessons on tech-enabled professional development. We shall be bringing you more insights and evidence in Part 2. Stay tuned!
KerkoCite.ItemAlsoKnownAs: 2339240:UHDL5L94 2405685:IPRDDKZN

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the Covid-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.
Accepted: 2022-05-18T23:30:06Z Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.17863/CAM.84697 2405685:8XW8JR6H

Teknolojia na maendeleo ya taaluma ya walimu nchini Tanzania: Zana za utafiti - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chacage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Aga Khan University, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza athari za programu ya maendeleo ya kitaaluma ya walimu kwenye matokeo ya masomo ya ngazi ya msingi. Zana zimetengenezwa na kufanyiwa majaribio makubwa katika warsha, pamoja na shuleni. Zana hizi zimetengenezwa kwa kuzingatia mifano mizuri kama vile zana ya Benki ya Dunia ya TEACH ya uchunguzi wa darasani, pamoja na miradi mingine ya utafiti ambayo timu imefanyia kazi. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao.
ZenodoArchiveID: 7701270 ZenodoArchiveConcept: 7701269 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7701270 10.53832/edtechhub.0149 2405685:6V4DBZR8
Keywords: _r:AddedByZotZen

Challenges encountered by teachers in supporting children with autism in primary schools in Tanzania - Ndunguru, N.E.; Kisanga, S.E. (Papers in Education and Development, 2023)
This paper reports the challenges experienced by teachers in supporting children with autism (CA) in primary schools in Tanzania. It is a qualitative study that employed purposive sampling technique to select seven primary school teachers of CA from two schools. Data were collected using a semi-structured interview and were analysed thematically. The findings of the study revealed that teachers experience challenges when supporting CA due to inadequate knowledge in managing the behaviours of CA. Also, teachers received little collaboration from parents of CA due to a lack of commitment to the education of their CA. The paper recommends for continuous professional development training to teachers of CA to enhance the acquisition of updated knowledge and skills for supporting CA. Also, there is a need for effective collaboration between teachers and parents for the successful support of CA.
KerkoCite.ItemAlsoKnownAs: 2339240:265RB2L2 2405685:TVG5APMB

Continuous Teacher Training Goes Nationwide in Tanzania - World Bank (World Bank, 2023)
A World Bank-funded program is piloting continuous professional development for primary school teachers in Tanzania.
KerkoCite.ItemAlsoKnownAs: 2339240:6CUKPF4H 2405685:RR47SXDT

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

Feasibility of a mobile phone training on autism spectrum disorders for teachers in Tanzania - Martino, Daniele C.; Naqvi, Nilofer C. (Technology, Pedagogy and Education, 2023)
Despite the rising global prevalence of autism spectrum disorders (ASD), significant disparities in ASD knowledge persist worldwide. Professional development trainings are effective in increasing teacher knowledge of ASD; however, in-person trainings pose accessibility concerns for teachers in low- and middle-income countries. In sub-Saharan Africa, few teacher development opportunities exist and logistical barriers limit attendance, highlighting the need for a more accessible training modality. The present study used a pre-post-test methodology among general and special education teachers in urban Tanzania to evaluate the feasibility of a mobile phone-delivered training on ASD. Results indicated a robust 84% participation rate and high quiz scores across training modules. The benefits of using mobile phone technology in a low-resource setting are presented. As the first asynchronous ASD training developed and implemented among teachers in Tanzania, this study can guide future research that explores how best to increase ASD knowledge among community members using technology.
Publisher: Routledge _eprint: https://doi.org/10.1080/1475939X.2023.2192517 KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2023.2192517 2339240:YYWSMV9B 2405685:24U764C8

Technology use in teacher preparation and professional development in low-and middle-income countries - UNESCO Digital Library - Hennessy, Sara; D'Angelo, Sophia; Koomar, Saalim; Kreimeia, Adam; Adam, Taskeen; Cao, Lydia; Haßler, Björn (UNESCO, 2023)
https://doi.org/10.54676/NJZV8067 KerkoCite.ItemAlsoKnownAs: 2339240:9URXV92S 2405685:UU8FCJCF

Introduction of an EdTech intervention to support learning of foundational skills in Sierra Leone: policy, teacher, and community perspectives - Lurvink, Anne-Fleur; Pitchford, Nicola J. (Frontiers in Education, 2023)
Background: Like many other countries, Sierra Leone faces significant challenges with primary education resulting in many children leaving primary school without acquiring basic foundational skills. To address these challenges, an educational technology (EdTech) intervention was implemented in 20 primary schools located in two marginalized districts in Sierra Leone. While this EdTech intervention has been shown to raise learning outcomes, little is known about the impacts on the broader education ecosystem. This paper investigates how this EdTech intervention might address some the challenges faced with primary education in Sierra Leone, by examining policy, teacher, and community perspectives. Method: A mixed methods approach was employed which included a policy mapping exercise, a survey of teachers training needs in supporting the development of foundational skills with grade 1 learners, an interview with teachers after they had delivered the EdTech intervention to garner their perceptions and experiences of using the technology in their class, and focus groups with teachers and other community members to gain insights into how the EdTech intervention had been received. Results: Findings from the policy mapping exercise and quantitative data from the survey of teacher training needs were triangulated with qualitative data from the interviews and focus groups. Four key themes emerged relating to the effective and sustained use of this EdTech intervention to support the acquisition of foundational skills by primary school children in Sierra Leone: (1) the need for continued teacher professional development, (2) the use of English as the language of instruction, (3) access to the technology by children with special educational needs and disabilities (SEND), and (4) the importance of active community engagement in supporting the intervention. Discussion: Collectively, results indicated that the EdTech intervention employed in this study aligned well to the education policy in Sierra Leone. Enhanced teacher training is needed, especially in using English as the language of instruction, and continued community engagement is essential for scaling the intervention effectively and ensuring that all children, including those with SEND, access the technology at primary school. These results have implications for other EdTech intervention deployed in resource-poor settings to enhance learning of foundational skills.
KerkoCite.ItemAlsoKnownAs: 2339240:J83HRBE6 2405685:BTDXQFJ9

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521375 ZenodoArchiveConcept: 7521374 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521375 10.53832/edtechhub.0154 2405685:AHVWDNGT
Keywords: _r:AddedByZotZen

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7781293 ZenodoArchiveConcept: 7781292 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7781293 10.53832/edtechhub.0159 2405685:GS45WQWR
Keywords: _r:AddedByZotZen

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8354887 ZenodoArchiveConcept: 8354886 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8354887 10.53832/edtechhub.0176 2405685:JNH4277Z
Keywords: _r:AddedByZotZen

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8208265 ZenodoArchiveConcept: 8208264 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8208265 10.53832/edtechhub.0057 10.53832/edtechhub.0173 2405685:47KMRR48 2405685:N2E79MUD
Keywords: _r:AddedByZotZen

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the COVID-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion, and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.
KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2023.2201590 2339240:KR923MEV 2405685:NRTU24IH

Analysis of emergency remote teaching in formal education: Crosschecking three contemporary techno-pedagogical frameworks - Kasperski, Ronen; Porat, Erez; Blau, Ina (Research in Learning Technology, 2023)
During the COVID-19 pandemic outbreak many countries around the world were forced to turn to Emergency Remote Teaching (ERT) and upscale the use of digital technologies for learning, teaching and assessment. The current study analysed field reports from 89 elementary and secondary Hebrew-speaking and Arabic-speaking information and communication technology schools in Israel, representing the cultural, ethnic, and religious diversity of the education system. The qualitative analysis of the collected data was based on three well established contemporary models of technology integration and Digital Competence of Educators (DigCompEdu): the International Society for Technology in Education, Technological Pedagogical Content Knowledge and DigCompEdu. The analysis (n = 872 statements) yielded aspects in the teachers’ reports that correspond with the theoretical models, alongside aspects that extend these models to ERT and aspects that were missing from the reports. Finally, based on our findings and previous work we suggested a comprehensive framework for ERT that can be used to design teachers’ professional development necessary for effective remote teaching in both emergency and routine times.
KerkoCite.ItemAlsoKnownAs: 10.25304/rlt.v31.2982 2339240:ANPQTXHM 2405685:8BBFIQT8
Keywords: COVID-19 pandemic; digital pedagogy; e-learning; emergency remote teaching; information and communication technology; online learning

Report of Case Studies on Responses to the Covid-19 Pandemic in Africa’s Educational Systems - Kiru, Elisheba; Ochieng, Vollan; Wawire, Brenda; Habiamana, Oliver; Ngware, Moses (APHRC, 2023)
This report presents case studies from seven African countries (i.e., Burkina Faso, Kenya, Malawi, Mali, Mozambique, Niger, and Nigeria) that implemented programs and innovations in response to the effects of the COVID-19 pandemic on the education systems. The report provides insights into building resilience within Africa’s education systems for the future. The case studies fill existing knowledge gaps on promising practices and add value to discussions on the contextual drivers that facilitated the implementation of the interventions, including active government involvement in mobilizing and supporting the initiatives. The programs include the PRONAE national school feeding program in Mozambique, the online teacher professional development program in Kenya, teacher training in Niger, back-to-school campaigns in Malawi, basic education training in internally displaced camps in Burkina Faso and Niger, and initiatives addressing sexual and gender-based violence in Mali. The case studies also seek to examine the extent to which the interventions addressed gender, equity, and inclusion. For the Global Partnership for Education (GPE) partner countries, these case studies provide valuable information regarding the operations of education systems and the well-being of learners.
Accepted: 2023-09-06T13:30:22Z KerkoCite.ItemAlsoKnownAs: 2339240:KW99KLTL 2405685:7V8V344E

Education in times of restriction: an examination of refugee girls’ and young women’s access to learning during COVID-19 school closures in Pakistan - Barnes, Katrina; Ashlee, Amy; Mukankusi, Aimee; Pacitto, Julia; Rabi, Asma; Thomas, Matt; Ullah, Noor; Zazai, Rozina; Zhao, Annette (Educational Research for Policy and Practice, 2023)
This paper examines the extent to which refugee girls and young women were able to access learning during COVID-19 education closures in Pakistan, and the role that EdTech played in their learning access. It is based on findings from a survey with 403 Afghan refugee students, along with in-depth interviews with six young female refugees. The research shows that, while the majority of female refugee students were able to continue accessing education in some form during school closures, learning access was nevertheless limited, and a sizable minority were not engaged in any learning during this time. Teacher and institutional support was either absent or inadequate for many students, and infrastructure and devices that serve to support remote learning were not always reliable or accessible. Although male respondents were less likely than females to engage in independent study during the closures, refugee girls and young women were significantly less likely than their male counterparts to own the devices they needed for learning. The findings demonstrate how targeted investment in specific types of EdTech and teacher professional development, as well as supporting educational institutions in the establishment of remote learning opportunities, could help sustain learning during future periods of educational restriction.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10671-023-09353-4 2405685:SWPGW69K
Keywords: COVID-19; Distance education; Educational technology; Gender; Pakistan; Refugee education

Primary school learning in sub-Saharan Africa during COVID-19: A scoping review of responses and recovery initiatives induced during school closures - Wawire, Brenda; Barnes-Story, Adrienne; Kiru, Elisheba; Kim, Sungkyum (Current Issues in Comparative Education, 2023)
Globally, the COVID-19 pandemic caused unprecedented disruptions in education. School closures quickly followed the onset of the pandemic to contain the spread of the virus, forcing millions of students out of their regular academic calendars. Countries put in place interventions aimed to reduce the deleterious effects of school closures and disruptions in learning. For instance, many countries used various mediums to provide students with distance learning. This scoping review examines the interventions that education systems in low- and middle-income Sub-Saharan African (SSA) countries (LMIC) implemented to mitigate learning loss in reading and writing skills among early grade learners (i.e., children attending primary schools) and discusses the reach of those programs. This review highlights the proportion of students reached by the targeted mitigation measures, revealing that LMIC countries in SSA provided students with remote learning opportunities through radio and television programming, provided teachers with professional development on the use of novel tools, and provided parents and families with support to help learners at home. However, these disruptions affected the traditional assessment methods. Various assessment methods were implemented to measure student progress, but there is a need for appropriate progress monitoring tools and accurate data to measure the effectiveness of the interventions. Many LMIC implemented Return-to-School policy frameworks, processes, and principles that ensured safe learning continuity.
Number: 1 KerkoCite.ItemAlsoKnownAs: 10.52214/cice.v25i1.9969 2339240:JJCSJBZX 2405685:Q4MW8X56
Keywords: COVID-19; early grades; interventions; learning loss; literacy; responses